2020
DOI: 10.1155/2020/8876807
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Authentication Protocol for D2D Communication in m-Health with Trust Evaluation

Abstract: Relay-assisted device-to-device (D2D) communication serves users at the edge of system coverage of 5G networks, enabling communication among sensors and patients’ mobile devices, and improving spectral and power efficiency. The security of D2D-based m-health applications requires attention due to the delicacy of the data treated in the collection, transmission, and storage of information on patients, whose devices must be adequately authenticated. However, traditional authentication and key agreement schemes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In 2020, Lopes, A.P.G., et al [20] suggested a lightweight and secure method based on Shamir secret sharing that is capable of providing robust security and reducing resource consumption (energy, processing). The manuscript also covers data relay and device discovery procedures.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, Lopes, A.P.G., et al [20] suggested a lightweight and secure method based on Shamir secret sharing that is capable of providing robust security and reducing resource consumption (energy, processing). The manuscript also covers data relay and device discovery procedures.…”
Section: Literature Surveymentioning
confidence: 99%
“…Use NS-3 or OMNET + + tools to simulate our protocol in order to assess the energy e ciency and impact of device mobility. [20] Lightweight and secure scheme…”
Section: Literature Surveymentioning
confidence: 99%
“…Because of the broadcast and open-air nature of a wireless channel, device-to-device (D2D) communications [1,2] are vulnerable to message eavesdropping and node impersonation [3][4][5][6]. To resist these attacks, an effective method is to encrypt sensitive data with secret session keys and send encrypted data via wireless channels.…”
Section: Introductionmentioning
confidence: 99%
“…(2) A new bit extraction method is proposed to improve the key generation rate and key entropy, which includes low entropy measurement elimination, random permutation, and adaptive multiple-bit extraction (3) Extensive experiments are conducted to evaluate the performance of the proposed scheme with both theoretical analysis and simulation. Experimental results show that the proposed scheme can achieve a higher key generation rate and key entropy compared with existing schemes.…”
Section: Introductionmentioning
confidence: 99%